“PROHIBICIÓN DE COLABORACIÓN EFICAZ A LOS SERVIDORES PÚBLICOS INMERSOS EN DELITOS CONTRA LA EFICIENCIA ADMINISTRACIÓN PÚBLICA”. - LOJAN RIOS, RONAL OMAR (2021)
The present degree thesis is entitled: "Prohibition of effective collaboration to public servants immersed in crimes against public administration efficiency", that arises from the necessity of its execution because in our Ecuadorian State these crimes in recent years have increased damaging the State funds and therefore the funds of our society, In addition, the public servants who carry out these crimes at the time they are processed avail themselves of effective cooperation that consists of a typified technical investigation in article 491 of the Comprehensive Organic Criminal Code in which they can reach an agreement with the Prosecutor's Office. for supplying data, instruments, effects, goods or precise, truthful and verifiable information in exchange for the reduction of their sentence in the sentence, allowing them to benefit from the reduction of the sentence up to 90%. Likewise, for the development of this thesis, materials and methods were applied, interviews and surveys were also carried out with legal professionals, results that served to propose a project to reform the Comprehensive Organic Criminal Code in its article 493 in regard to benefits of effective cooperation to prohibit public servants from availing themselves of said benefits, this reform will serve to guarantee the right to legal certainty and prevent the crime from remaining in impunity because the State's assets are compromised and the person responsible receives the penalty corresponding to the penal type.